Analytical Estimation of Self-Similar Wireless Traffic Relaxation Time and Hurst Coefficient Dependence - Yeryomin, R.; Petersons, E. (Elektronika ir Elektrotechnika, 2011)
Analyzed formula can be used for finding system relaxation time depending on what server load is and how high is input traffic self-similarity degree. It was found that the best result is achieved with Verhulst equation. Ill. 6, bibl. 6, tabl. 2 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.108.2.139